Students' Thinking Process in Solving Mathematical Literacy Problems in Islamic Contexts - Ramdani Miftah; Lia Kurniawati; Tatang Herman; Abdul Muin; Kadir Kadir (Universitas Sriwijaya, 2023)
Islamic contexts help stimulate students' mathematical abilities and develop their religious thinking. Therefore, this research aims to describe students' thinking process in solving mathematical literacy problems adapted from PISA questions using Islamic contexts. This research is qualitative-descriptive in nature with the purposive sampling technique used to select the three best teams competing on the National Mathematics Olympiad organized by the Mathematics Education Study Program of UIN Syarif Hidayatullah Jakarta in 2018. Each school level (Islamic elementary school (MI), Islamic junior high school (MTs), and Islamic senior high school (MA)) was represented by a team of 3 students. Data were collected through tests of mathematical literacy in Islamic contexts that matched PISA contexts and through interviews. Then, the data collected were analysed using triangulation techniques. The results showed that the students' thinking process in solving mathematical literacy problems in Islamic contexts was in accordance with Bayer’s thinking process theory. In general, the students already engaged in a thought process starting from information processing to decision-making. In fact, some MTs students had reached the thinking level of analysing relationships, synthesising problems or arguments, and conducting evaluations using several criteria suitable for the MA level. So it can be concluded that he Islamic contexts used in mathematical literacy questions tend to draw students' attention to the problems and help them solve those problems.